Design and development of self-adjusting fixed type jetty. Issue 4 (2nd October 2019) - Pandey, K. K.; Kumar, Rajesh; Pathak, Keshav; Patel, Ankit; Agrawal, Achin; Maurya, Aman Kr
Abstract : A jetty is one of the major components of port and terminal infrastructure which provides a deck to facilitate the movement of goods and ferries between land and ships, vessels, boats and similar systems. This paper discusses a novel concept of self-adjusting fixed type jetty (SAFTJ), targeting the engineering challenges being faced in the current jetty infrastructure globally. A SAFTJ is equipped with a self-adjusting mechanism to control the response of the structure against the fluctuating water level. This mechanism is governed and actuated by the natural forces (gravitational and buoyant force). A scaling law for the SAFTJ has been proposed. Based on the scaling law, a physical model has been designed, fabricated and tested in the laboratory to validate the concept of SAFTJ. The result of the physical model clearly demonstrates and conforms the operating mechanism of SAFTJ.